2002
DOI: 10.1081/css-120002767
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition and nutrient release of maize stover and groundnut haulm under tropical field conditions of malaysia

Abstract: Recycling of crop residues is essential to integrated and sustainable agricultural management system. Thus, it is of crucial importance to study the decomposition of these residues particularly in the humid-tropics. A litterbag experiment was carried out on an acid soil of the humid tropics of Malaysia. Haulm from groundnut and stover from were placed inside nylon 2 mm mesh bags (20 cm £ 20 cm) and placed on the soil surface in the field with a groundnut -maize rotation system. A total of 21 bags for maize and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 31 publications
(26 reference statements)
5
9
0
Order By: Relevance
“…The fast release of K in all treatment relative to other nutrient may be attributed to its existence in the cell fluid as non structural components (Christensen 1985). Similar results were reported by Mubarak et al (2002); Attiwell (1968);Christensen (1985).…”
Section: Discussionsupporting
confidence: 91%
“…The fast release of K in all treatment relative to other nutrient may be attributed to its existence in the cell fluid as non structural components (Christensen 1985). Similar results were reported by Mubarak et al (2002); Attiwell (1968);Christensen (1985).…”
Section: Discussionsupporting
confidence: 91%
“…Data from the present study corroborate those previously reported in the literature (Mubarak et al, 2002;Balkcom et al, 2004Balkcom et al, , 2007Meso et al, 2007) and suggest that the current Extension recommendations for N credits of 22 to 67 kg N ha -1 following peanut (Caddel et al, 2006;Buntin et al, 2007;Mitchell and Phillips, 2010;Jones et al, 2011;Maguire and Heckendorn, 2011;Wright et al, 2011;VDCR, 2014;Crozier et al, 2016) are overestimated. In addition, not all of the N released from peanut residue would be available to subsequent crops because of N cycling mechanisms, including immobilization and leaching (Knops et al, 2002), particularly on typical peanut-producing sandy soils with low cation exchange capacity.…”
Section: Nitrogen Mineralizationsupporting
confidence: 88%
“…However, crop residue benefits are only realized upon their decomposition and subsequent nutrient release which are influenced by their biochemical quality (Mubarak et al, 2002;Igbal, 2009). The quality of crop residues as a source of nutrients for plants depends on their nutrient concentration and amounts released on decomposition (Mwangi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%